Slow cooling versus episodic fluid injections: Deciphering the Caledonian orogeny in Vestvågøy, Lofoten islands, Norway - Fournier, Herbert W.; Lee, James K. W.; Camacho, Alfredo (Journal of Metamorphic Geology, 2019)
This is the peer reviewed version of the following article: Fournier, H. W., Lee, J. K. W., & Camacho, A. (2019). Slow cooling versus episodic fluid injections: Deciphering the Caledonian orogeny in Vestvågøy, Lofoten islands, Norway. Journal of Metamorphic Geology. doi:10.1111/jmg.12485, which has been published in final form at http://dx.doi.org/10.1111/jmg.12485. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions. The determination of the thermal (temperature–time) histories of high-P metamorphic terranes has been commonly based on the concepts of slow cooling and closure temperatures. In this paper, we find that this approach cannot reconcile a geochronological data set obtained from the amphibolite-facies allochthonous Leknes Group of the Lofoten islands, Norway, which reveals an extremely complex thermal history. Using detailed results from several different geochronometers such as 40Ar/39Ar, Rb–Sr and U–Pb, we show that a model invoking multiple, short-lived thermal pulses related to hot-fluid infiltration channelized by shear zones can reconcile this complicated data set. This model suggests that hot fluids infiltrated throughout basement shear zones and affected the overlying cold allochthon, partially resetting U/Pb rutile and titanite ages, crystallizing new zircon and produced identical 40Ar/39Ar and Rb/Sr ages in muscovite, biotite and amphibole in various rocks throughout the region. This paper shows the enormous potential of coupling laser Ar-spot data with thermal modelling to identify and constrain the duration of short-lived events. An optimal P–T–t history has been derived by modelling the age data from a previously dated large muscovite crystal (Hames & Andresen, 1996, Geology, 24:1005) and using Zr-in-rutile thermometry which is consistent with all geochronological data and geological constraints from the basement zones and allochthon cover. This tectonothermal model history suggests that there have ...